Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) ( 36 x 28 + 36 x 45 ) : 73
= 36 x (28 + 45 ):73
=36 x 73 :73
= 36 x (73 : 73)
= 36 x 1
= 36
b) ( 98 x 17 - 26 x 17 ) : 72
= 17 x (98-17):72
= 17 x 72 :72
=17 x (72 :72)
= 17 x 1
= 17
a) ( 36 x 28 + 36 x 45 ) : 73 = 36
b) ( 98 x 17 - 26 x 17 ) : 72 = 17
117 x 36 + 117 x 72 - 17 x 72 - 17 x 36
= ( 117 - 17 ) x 36 - ( 117 - 17 ) x 72
= 100 x 36 - 100 x 72
= 100 x ( 36 - 72 )
= 100 x -36
= -3600
____________________________________
408 x 53 - 5 x 204 - 204
= 408 x 53 - 5 x 204 - 204 x 1
= 408 x 53 - ( 5 - 1 ) x 204
= 408 x 53 - 4 x 204
= 21624 - 816
= 20808
1200 × 3 - ( 17 + x) = 36
3600 – (17 + x) = 36
17 + x = 3600 -36
17 + x = 3564
x = 3564 – 17
x = 3547
a. 1200 x 3 - ( 17 + x ) = 36
3600 - ( 17 + x ) = 36
17 + x = 3564
x = 3547
a, = 113 x (54+45+1) = 113 x 100 = 11300
b, = (36+62) x (117-17) = 98 x 100 = 9800
k mk nha
a. 1200 × 3 - ( 17 + x) = 36
3600 – (17 + x) = 36
17 + x = 3600 -36
17 + x = 3564
x = 3564 – 17
x = 3547
a. 1200 × 3 - ( 17 + x) = 36
3600 – (17 + x) = 36
17 + x = 3600 -36
17 + x = 3564
x = 3564 – 17
x = 3547
150 : 3 x ( 17 - x ) = 36
50 x ( 17 - x ) = 36
17 - x = 36 : 50
17 - x = 0,72
x = 17 - 0,72
x = 16,28
150 : 3 ( 17 - x ) = 36
50 ( 17 - x ) = 36
17 - x = 36 : 50
17 - x = 0,72
x = 17 - 0,72
x = 16,28